Evolving Gamaliel Tradition in Codex Bezae Cantabrigiensis, Acts 5:38-39: A Novel Application of Coherence-Based Genealogical Method (CBGM) - Hyytiäinen, Pasi (TC, 2019)
This article challenges the common scholarly conviction that Acts in Codex Bezae Cantabrigiensis (D05) represents a single cohesive textual tradition, arguing instead that D05 should be understood as an evolving text, consisting of multiple textual layers without any trace of unified editorial activity. The Coherence-Based Genealogical Method (CBGM), together with detailed internal considerations, is used to show that it is possible to differentiate intermediary variants in Acts 5:38â"39 between the shorter readings in B03 (Codex Vaticanus) and the longer ones in D05. Such intermediary textual stages are also found among the so-called Western readings, revealing how Gamaliel tradition gradually grew over time as new pieces were added to the text from various sources. These findings challenge the notion of the Western text as a definable textual entity.